Spatial compositional variations in Quaternary volcanic from the Northern Kuril Islands, Russia. - Bergal-Kuvikas Olga; Nakagawa Mitsuhiro; Avdeiko Gennady; Rashidov V.A. (My University, 2011)
The Northern Kuril Islands form the part of Kuril-Kamchatka volcanic arc. Approximately steady-state subduction beneath the islands occurred since the late Miocene (Avdeiko et al, 2006). We newly determined major and trace element compositions of number Quaternary rocks from 7 subarial and 3 submarine volcanoes (Fig. 1) - to demonstrate systematic changes in magma genesis across arc. Peculiarities of whole-rock chemistry, and petrography of these rocks enable us to divide of all volcanoes into five main groups. These volcanic groups have good correlation with geological data. Each unit of the volcanic group is characterized by narrow range of chemical variations (Fig. 2).
Keywords: Вулкан 1.3; Вулкан 1.4; 38.37.25 Вулканология; 38.37.27 Петрография океанических пород и подводный вулканизм; Эбеко; Алаид; Карпинского; Анциферова